Organization Of Educational Process and Development Of Educational Process In School - Artiqova Karomat Kamoldjonovna (Euro Asian Journal Publishing, 2024)
School or out-of-school educational facilities, pedagogues, social pedagogues are engaged in activities aimed at solving educational issues. This activity includes a student-centered effect that takes into account the characteristics of the environment. If we talk about the influence of the pedagogue on the student within the limits of the implementation of his professional duties, then we call such activity educational work
Keywords: Education; pedagogy; educational process